HATI YANG TERLUKA: PASTORAL KONSELING BAGI ORANG YANG MENGALAMI KEPAHITAN ATAU LUKA BATIN - Hesky C Opit (POIMEN Jurnal Pastoral Konseling, 2020)
Healing the inner wounds by forgiveness is an indispensable step for the recovery of one’s self so he/she can experience peace and prosperity. Both of patient (victim) and actors, need to realize and to confess honestly and openly— to heal—that he/she was actually suffering from the inner wounds that are embedded in the heart, which can even be experienced by a person since he/she was in the womb and therefore need to take immediate action to forgive. Considering that inner wounds are a problem that can be experienced by anyone and the resulting negative impact in one's life, then the research was conducted. The study, based on a literature review indicates that there is a strong correlation between inner wounds suffered by a person with a bad experience. Research also shows that the inner wounds can be healed by forgiveness. The study is expected to be contributing to problem-solving inner wounds caused by a person's past by forgiveness.